A amamentação sob o olhar de mães frequentadoras da atenção primária do município de Santos - Barros, Daniela Emmerich de [UNIFESP] (2014)
The act of breastfeeding goes beyond the physiological aspects related to nutrition. Although the benefits of exclusive breastfeeding (EBF) to the health of both mother and child are well known and therefore recommended for the first six months of the child's life, it is observed that many factors influence the achievement of this goal. Even with public policies and laws, which support, protect and encourage the EBF, they seem to be insufficient, since it is a process permeated by values, beliefs, desires, satisfactions, frustrations, among other feelings. The objectives of this study were to understand the process of interruption of exclusive breastfeeding in mothers attending primary care in Santos; to identify the profile of mothers who precociously interrupt exclusive breastfeeding or not; to identify the network of support for the continuation of breastfeeding, and to identify the influence of the social networking on the mother's decision to discontinue exclusive breastfeeding. In this descriptive, cross-sectional quantitative/qualitative study, 24 women, in the remote postpartum period, participated divided into two groups: mothers who prematurely discontinued the EBF (IP) and mothers without early discontinued EBF (NIP). Data collection took place in two stages: first, mothers of IP and NIP groups answered a questionnaire on demographic, status of birth and feeding characteristics. In the second, only the IP group mothers were interviewed regarding how the process of discontinuation of exclusive breastfeeding happened. Data were collected in the six health units in the city of Santos, in which the researcher works. Quantitative results are presented as descriptive statistics and for the comparison between IP and NIP groups the Fisher Exact Test (results significant when p <0,05) was applied. To analyze the qualitative results we used the method of the Collective Subject Discourse, in which, from key expressions of maternal speeches, and central ideas, it as possible do defined categories and speeches written in the first person of singular were identified, which reflect the ideas of the collective. Results indicated that mothers were mostly married or in a stable relationship, 30 years old or more, multiparous, having completed elementary school or incomplete middle school II, belonging to socioeconomic class C and not working. There was no difference between the socio-cultural, obstetric and postpartum resultds between IP and NIP groups, excepting the use of artificial teats before 6 months (p = 0,002), child?s father support (p= 0.036) and having no support (p=0.037) for the EBF. The analysis of the IP group discourse generated five categories: "The (in) sufficient breast," "When suffering speaks louder", "My knowledge and the knowledge of others: between breastfeeding and formula", "Disruption of the umbilical cord"and "Self-perception". For two categories dichotomous discourses were identified: the sovereignty of the bottle to the satisfaction of the child, and at the same time, the appreciation of the breast milk. Furthermore, it was observed that regarding the social network, the influence can be both positive and negative for the maintenance of EBF and that just to inform women about their benefits is not enough if people who surround her are not involved in the process, particularly the father. Healthcare professionals should ensure accurate information on EBF, be aware of the qualified listening and create a bond of trust. We conclude that looking at issues related to breastfeeding must go beyond the biological and technologic dimensions and also consider the social and cultural dimension, which both influence this process, in particular the network support of family and health care team.